Enoch Book of Watchers and Astronomical Book: Theodicy in the Context of a Proto-Scientific Cosmology - Evans, Annette (Journal for Semitics, 2017)
In the earliest book of 1 Enoch, the Astronomical Book, Enoch the â€œseerâ€ exhorts the reader to contemplate cosmological phenomena. The book displays a keen interest in cosmology and meticulous observation of the natural world. Such characteristics still today form the foundation of the discipline of science. The second earliest Enochian writing, 1 Enoch Book of Watchers, in addition to proto-scientific observations, propounds an alternative explanation for the existence of evil to the traditional Christian belief in the doctrine of â€œoriginal sinâ€ as a result of the â€œfallâ€ of Adam and Eve. The origin of evil is recognised to be divine, but the deity is exonerated from responsibility for it. There is an intriguing relation between the observations of natural phenomena, cosmology, divination, and angelic activity in these earliest Jewish apocalypses. This article considers the striking similarity between the use of proto-scientific elements in this pseudepigraphical literature to offer a solution to the vexed problem of theodicy, and the scientific observations that culminated more than two thousand years later in the new paradigm of evolution as the means of creation, and hence for understanding the inevitability of suffering and evil in cosmological terms.